HRD Interventions that Offer a Solution to Work-Life Conflict. Issue 2 (May 2021) - Hammer, Emily
The Problem: Balancing work and life can be difficult. In a new world of work amidst COVID-19, balancing work and life has become even more challenging. Employees are struggling to adjust their work-life obligations while maintaining performance expectations. Providing employee support to reduce stress and minimize adverse effects on performance outcomes requires employer action. The Solution: HRD interventions are recommended as organizational support mechanisms. These interventions are designed to reduce stress produced by work life conflict, particularly during stressful organizational events. Through organizational support, employees are offered the opportunity to increase individual performance. The Stakeholders: HRD and HRM professionals, scholars, organizational planners, organizational leaders and managers, and all others who have a vested interest in employee well-being.